Characterization of Thermal Properties of Pig Hair Fiber. Issue 4 (4th July 2017) - Mohan, N. H.; Ammayappan, L.; Sarma, D. K.; Debnath, S.; Tamuli, M. K.
ABSTRACT: Hair fiber is a key by-product of humane slaughter of pigs with considerable economic value. In the present study, we investigated the thermal properties of pig hair fiber using Differential Scanning Calorimetry (DSC) and thermogravimetric analysis (TGA). The DSC curve showed a broad endotherm (around 50–80°C) initially, followed by denaturation doublet peaks (229°C and 239°C) and finally a pyrolysis endotherm. The melting enthalpy of pig hair fiber was 9.93 J/g on dry basis. During TGA, distinct phases of initial weight loss due to loss of moisture and later through thermal degradation of protein around 238–240°C were observed. Mean thermal insulation and conductivity values of pig hair fiber were 0.068 ± 0.004 m 2 K/W and 0.029 ± 0.003 W/m/K, respectively. The thermal characteristics of pig hair fiber were similar to other keratin fibers of animal origin.